2013
DOI: 10.1038/bjc.2013.489
|View full text |Cite
|
Sign up to set email alerts
|

Maspin is a marker for early recurrence in primary stage III and IV colorectal cancer

Abstract: Background:Little is known about the factors that drive metastasis formation in colorectal cancer (CRC). Here, we set out to identify genes and proteins in patients with colorectal liver metastases that correlate with early disease recurrence. Such factors may predict a propensity for metastasis in earlier stages of CRC.Methods:Gene expression profiling and proteomics were used to identify differentially expressed genes/proteins in resected liver metastases that recurred within 6 months following liver surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…f Average quantification of the wound closure in two independent experiments performed Arch Dermatol Res cancer cells [25]. However, Maspin protein has also been linked with recurrence and metastatic risk in breast [38,51], colorectal [39] and bladder cancer [2], and elevated Maspin levels correlates with good prognosis in esophageal [45] and oral SCC [47]. Moreover, a decreased expression of Maspin has recently been demonstrated to correlate with an increased malignancy of mouse and human tumor epidermal cells [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…f Average quantification of the wound closure in two independent experiments performed Arch Dermatol Res cancer cells [25]. However, Maspin protein has also been linked with recurrence and metastatic risk in breast [38,51], colorectal [39] and bladder cancer [2], and elevated Maspin levels correlates with good prognosis in esophageal [45] and oral SCC [47]. Moreover, a decreased expression of Maspin has recently been demonstrated to correlate with an increased malignancy of mouse and human tumor epidermal cells [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Maspin can inhibit serine protease, and several studies have demonstrated that maspin can inhibit tumor growth by inducing apoptosis (14,15). In certain types of tumor, maspin is often expressed at low levels (16).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced expression of maspin is correlated with unfavorable prognosis in pancreatic, ovarian and colorectal cancer (8)(9)(10). High maspin expression correlates with an unfavorable outcome in colorectal cancer in stage III and IV, suggesting that maspin may have a stage-specific function possibly associated with cancer cell dissemination and/or metastatic outgrowth (11). The maspin expression in the cytoplasm has recently been reported as an independent unfavorable prognostic indicator of patients with lung adenocarcinoma with tumor size <3 cm (12).…”
Section: Introductionmentioning
confidence: 99%